2007
DOI: 10.1121/1.2749442
|View full text |Cite
|
Sign up to set email alerts
|

Experimental detection and focusing in shallow water by decomposition of the time reversal operator

Abstract: A rigid 24-element source-receiver array in the 10-15 kHz frequency band, connected to a programmable electronic system, was deployed in the Bay of Brest during spring 2005. In this 10- to 18-m-deep environment, backscattered data from submerged targets were recorded. Successful detection and focusing experiments in very shallow water using the decomposition of the time reversal operator (DORT method) are shown. The ability of the DORT method to separate the echo of a target from reverberation as well as the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 14 publications
0
33
0
Order By: Relevance
“…Indeed, the SVD permits the decomposition into orthogonal signal and noise subspaces. It has been shown that the SNR increases as the square-root of the number of antennas for a given power emitted by the Tx array [9]. Furthermore, the use of the MUSIC estimator, unlike classical time reversal, allows the resolution of two close scatterers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the SVD permits the decomposition into orthogonal signal and noise subspaces. It has been shown that the SNR increases as the square-root of the number of antennas for a given power emitted by the Tx array [9]. Furthermore, the use of the MUSIC estimator, unlike classical time reversal, allows the resolution of two close scatterers.…”
Section: Discussionmentioning
confidence: 99%
“…The method was first developed for ultrasonic applications with arrays of piezo-electric transceivers [6][7][8]. It has shown its efficiency in several domains like non-destructive evaluation [8], detection in shallow water [9] and medical imaging [10]. The DORT method can be applied to all types of linear waves and has been employed in electromagnetism since 2001 [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that the number of nonzero singular values (SVs) of the MDM provides the number of point-like targets and the corresponding singular vectors give the monochromatic Green function from the array to the targets associated. 10,13,14 Indeed at pulsation frequency , the singular vector u p is related to the Green's function G p connecting the array to the pth target's position r p by…”
Section: Phase Synchronization Of the Eigenvectors Of Tro: Theorymentioning
confidence: 99%
“…To solve the above problem, an echo-to-reverberation enhancement method based on decomposition of the time reversal operator (DORT) [12][13][14][15][16] with forward and backward reverberation nulling has been proposed [17]. This method can focus sound energy at the target while nulling the energy at the bottom near the target range simultaneously, substantially enhancing the echo-to-reverberation ratio without a probe source and prior knowledge about the relative scattering intensity of target and bottom.…”
mentioning
confidence: 99%